Improvement of Pantun Writing Skills with Serial Writing Method Integrated with Smart Card Media - Miftakhul Firman Ferdiansyah Efendi (Universal Education Jurnal Teaching and Learning, 2024)
This study aims to improve pantun writing skills through Classroom Action Research (PTK) activities. This research was conducted at Senior High School (SMAN) 1 Sidayu, Gresik, of XI grade as many as 36 students. The research was conducted for 2 cycles. The instrument used in this study was a description test that assessed four aspects, namely content, text structure, line cohesiveness, and linguistic rules. The results showed that students' skills in writing rhymes increased based on the average score, which increased from 57.94 to 71.94. This can also be seen from the increasing number of students who get adequate and good score categories and those who get scores in the lower category, which decreases.